1995
DOI: 10.1108/09642369310095210
|View full text |Cite
|
Sign up to set email alerts
|

Managing innovation and risk

Abstract: Many companies still do not innovate to match customers′ needs. Suggests that to achieve competitive advantage a product innovation matrix should be developed to help marketing and technology staff to think in terms of innovation for the customer. Risks need to be managed from the beginning by identifying them, assessing their likelihood and possible impact, and preparing an overall action plan to deal with them. Suggests several prerequisites to make innovation safer and faster. Outlines various tools and tec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 0 publications
0
9
0
Order By: Relevance
“…The analysis and management of such risks can be translated into activities that aim to assist the capacity of such companies to anticipate how they will deal with the uncertain environment of the market analyzed, by fostering actions that may well come to contribute to the company's bottom line (Mortimer, 1995). O'Connor et al (2008) indicate that the advance of innovations demands that companies be encouraged to deal systematically with the risks to which they are exposed, with a view to reconciling the high degree of uncertainty and dynamic and flexible environments that enables innovation to make successful advances.…”
Section: Innovation and Risk Management Modelsmentioning
confidence: 99%
See 2 more Smart Citations
“…The analysis and management of such risks can be translated into activities that aim to assist the capacity of such companies to anticipate how they will deal with the uncertain environment of the market analyzed, by fostering actions that may well come to contribute to the company's bottom line (Mortimer, 1995). O'Connor et al (2008) indicate that the advance of innovations demands that companies be encouraged to deal systematically with the risks to which they are exposed, with a view to reconciling the high degree of uncertainty and dynamic and flexible environments that enables innovation to make successful advances.…”
Section: Innovation and Risk Management Modelsmentioning
confidence: 99%
“…Due to the swift advance of this market as well as the volume of businesses regarded as innovatory, there is high degree of uncertainty about the internal evolution factors of development of innovative business, and external (macroeconomic and market issues) which stresses the real challenge inherent in the process to manage innovation (Bessant, 2003;Mortimer, 1995;Viana, 2012;Nagano et al, 2014). The uncertainty mentioned has been present ever since innovative companies were formed, which therefore sees to it that the activity of…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…when considering a market in which innovation is more demanding. In addition, according to the previous author, QFD has two additional counter‐effects that can help crush innovation:since it uses up a lot of resources identifying customer requirements and filling out the matrices, there is not much time left for coming up with new ideas; andit can enforce a linear way of thinking about product development that leaves little margin for the type of unconstrained thinking from which innovation flows.Although those previous effects can inhibit innovation, to make it safer and faster, Kodak has found that among several other prerequisites to satisfy, the origin of an idea origin must relate to real customer need (Lee‐Mortimer, 1995) and QFD is a method for understanding customer outcomes (Killen et al , 2005) and a way of concisely structuring communication and linking together information (Govers, 1996) to develop comprehensive product specifications.…”
Section: Qfd For Innovative Productsmentioning
confidence: 99%
“…In addition, the companies must have a process for innovating to match customer needs (Lee‐Mortimer, 1995). In measuring a company's innovation potential, it is important to look at the tools and methods utilised in the innovation efforts (Davidsen, 2004).…”
Section: Introductionmentioning
confidence: 99%